Emptiness formation probability for the spin-1/2 XX chain with three spin and uniform long-range interactions - Lou, P.; Lee, J.Y. (Condensed Matter Physics, 2007)
The emptiness formation probability (EFP) that the first n spins of the chain are all aligned downwards is studied for the one-dimensional spin- 1/2 XX chain system with both critical and non-critical regimes with three spin and uniform long-range interactions. By using the emptiness formation probability P(n), the block-block entanglement Sn and the magnetization Mz, the properties of the system are also studied. It is worthy of note that when the quantum phase transition from the phase III to the phase II occurs, the Emptiness Formation Probability P(n) of the system decreases, but the block-block entanglement Sn increases.